Improving classroom formative assessment through Innovative instruments at Angel Tinoco Ruiz School. - Montenegro Ordóñez, Lady Marietha (2018)
Unidad Educativa Angel Tinoco Ruiz was studied through a research study. First, the literature review has shown a revision of the assessment kinds. It was mainly focused on formative assessment procedure applied by English teachers. Additionally, the importance of formativeassessment as teachers’ role and how to improve the leaners’ achievement goals. This project has also provided results of how teachers’ work in class during formative assessment. The research was conducted by a survey as the instrument to collect data and the analysis of information has shown that teachersneed to get first of all a clear idea of formative assessment process, after that, the application of technology in class to call the students attention to increase the academic proficiency. Finally, a proposal was designed as apossible solution to improve teaching practice.